2017
DOI: 10.9778/cmajo.20170018
|View full text |Cite
|
Sign up to set email alerts
|

Costs of services for homeless people with mental illness in 5 Canadian cities: a large prospective follow-up study

Abstract: A n estimated 35 000 Canadians are homeless on any given night, and over 235 000 experience homelessness over the course of a year. 1 In some jurisdictions, the discussion has shifted toward how homelessness can be ended rather than on how to manage it.1,2 Ending homelessness will require resources in the form of targeted prevention interventions, 2 development of affordable housing and a variety of housing and support programs such as Housing First, in which homeless people are offered immediate access to per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 28 publications
0
53
0
Order By: Relevance
“…Housing First programs include intensive supports and follow-up similar to those of Assertive Community Treatment (ACT) teams and have been evaluated with randomized control trials (RCT) designs. RCT studies found the Housing First model to be more effective and efficient compared to other housing programs, in the United States [ 3 ] and Canada [ 4 ]. In fact, better effectiveness has been shown through housing stability as well as reduction in hospitalization, juridical system contact and symptoms [ 3 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Housing First programs include intensive supports and follow-up similar to those of Assertive Community Treatment (ACT) teams and have been evaluated with randomized control trials (RCT) designs. RCT studies found the Housing First model to be more effective and efficient compared to other housing programs, in the United States [ 3 ] and Canada [ 4 ]. In fact, better effectiveness has been shown through housing stability as well as reduction in hospitalization, juridical system contact and symptoms [ 3 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The success of these programs has been well documented (Stergiopoulos et al 2014;Corbiere et al 2010). However, at the same time, increasing numbers of people who are homeless or marginally housed are presenting to emergency departments (Latimer et al 2017). As well, in Vancouver, British Columbia, the number of people who are at risk of homelessness continues to escalate: the highest numbers to date were reported in 2017, with a 30% increase compared to 2014 (BC Non-Profit Housing Association and M. Thomson Consulting 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Housing instability and especially homelessness, which is an acute form of housing instability, are associated with a range of adverse health outcomes and increased costs for health care systems . This knowledge has led to growing recognition of housing as an important social determinant of health and a corresponding increase in efforts of health care systems to address housing instability and homelessness, ranging from interventions in clinical settings, to new care delivery, and financing mechanisms …”
Section: Introductionmentioning
confidence: 99%
“…
| INTRODUC TI ONHousing instability and especially homelessness, which is an acute form of housing instability, are associated with a range of adverse health outcomes 1,2 and increased costs for health care systems. [3][4][5] This knowledge has led to growing recognition of housing as an important social determinant of health 6 and a corresponding increase in efforts of health care systems to address housing instability and homelessness, ranging from interventions in clinical settings, 7 to new care delivery, 8 and financing mechanisms. 9From a practical standpoint, efforts to address housing instability within the health care system rely on the accurate identification of those who are, or are at risk of, experiencing housing instability.Accurate identification can lead to more efficient targeting of interventions to prevent housing instability or to mitigate the potential ill effects of continued housing instability.
…”
mentioning
confidence: 99%